Business Development Strategy With A Swot Analysis Approach In Increasing Company Income (Study On Cars’n Kidz Convection, Sidorejo Village Jabung District, Malang Regency) - Chanafi, Ainul; Widayawati, Eny (Program Pascasarjana STIE Amkop Makassar, 2024)
Abstract This study aims to determine the right business development strategy so that it can be used by Cars'n kidz convection to expand its market share and increase sales. Cars'N Kidz is a children's clothing convection business in Jabung District, Malang Regency. To find out the right strategy in increasing sales, researchers use SWOT analysis. This type of research uses qualitative descriptive and observation, interviews, and literature reviews as data collection methods. The results of this study obtained data that based on the Cartesian diagram shows that Cars'n Kidz is in the Growth quadrant where the quadrant is a very profitable situation. This is because Cars’N Kidz Convection are in a growth position so it is important to utilize strengths and take existing opportunities, the strategy consists of:1) Improving product quality and collection. 2) Forming an association/union of convection entrepreneurs to maintain a bargaining position with suppliers. Keywords: SWOT, Convection, Business Strategy, IFAS and EFAS Matrix.